Reproductive factors and lung cancer risk: a comprehensive systematic review and meta-analysis - Xin Yin; Zhiying Zhu; H. Dean Hosgood; Qing Lan; Wei Jie Seow (BMC, 2020)
Abstract Background A number of studies have investigated the association between reproductive factors and lung cancer risk, however findings are inconsistent. This meta-analysis aimed to evaluate the association between female reproductive factors and lung cancer risk. Methods We conducted a comprehensive systematic search to identify relevant and eligible studies published before 18th December 2019. Inter-study heterogeneity was assessed using the Q test and I 2 statistic. Based on the heterogeneity of each reproductive factor, fixed or random effects models were used to calculate the summary odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup analyses by study design, lung cancer subtypes, smoking status, and ethnicity were also performed. Results A total of 66 studies with 20 distinct reproductive factors were included in this meta-analysis. Comparing the highest and lowest categories (reference) of each reproductive factor, parity (OR = 0.83, 95% CI = 0.72-0.96), menstrual cycle length (OR = 0.79, 95% CI = 0.65-0.96), and age at first birth (OR = 0.85, 95% CI = 0.74-0.98), were significantly associated with a lower risk of overall lung cancer. On the contrary, non-natural menopause was significantly associated with higher lung cancer risk (OR = 1.52, 95% CI = 1.25-1.86). Among never-smokers, a significant negative association was found between parity and lung cancer risk. Both parity and non-natural menopause were statistically significant in case-control studies. Conclusion These results suggest that certain reproductive factors may be associated with lung cancer risk. Future studies should further validate the associations, and investigate the underlying mechanisms.